MENINGKATKAN KEPERCAYAAN DIRI ANGGOTA PMR DALAM BERPENDAPAT DAN TAMPIL MELALUI BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING DI SMPN 14 BANJARMASIN - Oktavia, Wilda; Elfa Khairun Nisya; Indriyanti Rosy Pratama; Ali Rachman; Kartasiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low self-confidence is one of the main obstacles preventing students from expressing opinions and performing in public, particularly among students involved in the Youth Red Cross (PMR) extracurricular program at school. This research aims to improve the self-confidence of PMR (Youth Red Cross) members in expressing opinions and performing in public through group guidance using role-playing techniques at SMPN 14 Banjarmasin. This school counseling action research was conducted collaboratively with three observers across three cycles involving ten PMR members at SMPN 14 Banjarmasin, using rating-scale observation sheets and a self-confidence questionnaire as data collection instruments, analyzed through comparative descriptive analysis across cycles. The results showed a gradual improvement in all confidence indicators from the pre-cycle stage through the third cycle, with all indicators eventually exceeding the established success threshold by the final cycle. These findings confirm that group guidance with the role-playing technique is effective as a gradual intervention for building the courage to perform and speak up among students involved in school organizations.